2018
DOI: 10.1042/bst20170467
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase δ (PI3Kδ) in respiratory disease

Abstract: Defining features of chronic airway diseases include abnormal and persistent inflammatory processes, impaired airway epithelial integrity and function, and increased susceptibility to recurrent respiratory infections. Phosphoinositide 3-kinases (PI3K) are lipid kinases, which contribute to multiple physiological and pathological processes within the airway, with abnormal PI3K signalling contributing to the pathogenesis of several respiratory diseases. Consequently, the potential benefit of targeting PI3K isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Furthermore, particularly in terms of the role of PI3K-δ in the effector function of various immune cells, inhibition of PI3K-δ has been shown to effectively suppress TH1/TH17 cytokines and TNFα in numerous pathologic conditions, including allergic airway disease [42,65], autoimmune and inflammatory arthritis/dermatitis [35,66], and neuroinflammation associated with ischemia/reperfusion [67], which involves diverse cell types (e.g., naïve/memory T cells, various TH cells, IL-17 producing TCRγδ T cells, and macrophages) crucial for neutrophilic inflammation [68]. As for neutrophilic inflammation, per se, PI3K has been known to influence several key functional aspects including chemotaxis, oxidative burst, and survival of neutrophils [14]. In particular, the crucial roles of PI3K-δ in the regulation of neutrophil trafficking and directional movement [69,70] and effector function such as oxidative burst [71] have been demonstrated.…”
Section: Roles Of Pi3k-δ In Non-type 2 Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, particularly in terms of the role of PI3K-δ in the effector function of various immune cells, inhibition of PI3K-δ has been shown to effectively suppress TH1/TH17 cytokines and TNFα in numerous pathologic conditions, including allergic airway disease [42,65], autoimmune and inflammatory arthritis/dermatitis [35,66], and neuroinflammation associated with ischemia/reperfusion [67], which involves diverse cell types (e.g., naïve/memory T cells, various TH cells, IL-17 producing TCRγδ T cells, and macrophages) crucial for neutrophilic inflammation [68]. As for neutrophilic inflammation, per se, PI3K has been known to influence several key functional aspects including chemotaxis, oxidative burst, and survival of neutrophils [14]. In particular, the crucial roles of PI3K-δ in the regulation of neutrophil trafficking and directional movement [69,70] and effector function such as oxidative burst [71] have been demonstrated.…”
Section: Roles Of Pi3k-δ In Non-type 2 Inflammationmentioning
confidence: 99%
“…However, expression of p110δ and p110γ isoforms is predominantly restricted in hematogenous immune and inflammatory cells, and these isoforms are the dominant class I PI3K isoforms in leukocytes, which implies their critical involvement in various facets of the innate and adaptive immune system and their potential as druggable targets for developing PI3K-targeted therapies. As for pulmonary disorders, the p110δ isoform has been shown to play important roles in the inflammatory process of bronchial asthma and chronic obstructive pulmonary disease, especially in mediating CS resistance [13,14,15,16]. Furthermore, a recently described immune deficiency in humans, the activated PI3K-δ syndrome (APDS) (e.g., several point mutations occur in the p110δ catalytic domain, leading to exaggerated PI3K-δ signaling), clearly demonstrates the clinical outcomes associated with aberrant activation of PI3K-δ, including recurrent respiratory infections, airway damage and the extremely high incidence of bronchiectasis, and dysfunctional T and B lymphocytes, all of which highlight the critical role of this isoform, particularly in the respiratory system [17,18].…”
Section: Introduction To Class I Pi3k and Its Isoformsmentioning
confidence: 99%
“…Pharmacological studies together with genetic evidence have implicated dysfunctional PI3K signaling in airway inflammation, and studies exploring the potential therapeutic benefit of PI3Kδ (class IA isoform) have yielded encouraging results (43). PI3Kδ is an isoform of PI3Kγ and lies downstream of tyrosine kinase-associated receptors, T cell receptors (TCR), co-stimulatory, and cytokine receptors, depending on the cell type.…”
Section: Pi3-kinases Regulate Il-17 Secretion and T-cell Expansionmentioning
confidence: 99%
“…It was observed that therapies directed at neutrophil-derived products have limited efficacy and are only effective exceptional circumstances (60, 61). The p110δ isoform has been implicated in airway inflammation, with selective targeting of this isoform yielding promising results in COPD and asthma by broadly reducing lymphocyte-derived cytokines such as IL-17A, and suppressing ROS release from neutrophils (43, 62, 63). Specifically, p110δ inhibition demonstrates that T lymphocyte-derived cytokine generation can be suppressed with multiple T-cell lineages targeted (48), as well as Th17 differentiation (48).…”
Section: Is the Inhibition Of P110δ Isoform An Option For The Treatmementioning
confidence: 99%
“…PI3K as lipid kinases play role to maintain normal function of airway. Abnormal PI3K signaling can alter airway function, so that inflammatory responses are aggravated [129]. Such a condition is seen in patients with respiratory diseases especially allergic inflammation and asthma.…”
Section: Potential Mechanisms Of Respiratory Manifestations In Apdsmentioning
confidence: 99%